The influence of flavoring components on the physicochemical properties of spray-dried high oleic (HO) and tofu line (TL) soymilk powder - Singh, P.; Krishnaswamy, K. (Frontiers in Food Science and Technology, 2023)
With the increased interest in plant-based foods, a growing demand for high protein plant-based alternatives has spiked the food industry. Consumer acceptance of a food product is influenced by the natural flavor or through the addition of familiar flavors, which influence the purchase of the food product. There is a wide variety of soy-based products available on the market, with soymilk being one of the most popular among vegetarian diets. Soybean products have been known for their beany or malty flavor, having advantage in certain types of food products like tofu yet experiencing market resistance among certain population groups that are unfamiliar with the beany flavor of soybean. Improving the flavor profile might significantly change consumer perceptions toward soy-based food products. In the current study, chocolate and vanilla flavors were added to newly developed varieties of soybean milk (high oleic and tofu line) to investigate the impact of flavoring components on the physicochemical characteristics of novel soybean varieties. Soymilk with flavoring components were spray-dried, and the resultant powders were subjected to physical, reconstitution, rheological, particle, and thermal property analysis. Experimental analysis and statistical data showed that powder properties were improved with the addition of flavoring components. Obtained product yield (57%–66%), flowability (good to passable), wettability (2.52–1.34 min), dispersibility (83%–95%), solubility (75%–86%), viscosity (3.22–10.35 mPa s), thermal stability (≥15°C), particle size distribution (improved homogeneity), and morphology (smooth and spherical). The obtained results would be of interest to food processors and food product developers looking for plant-based alternatives.